2012
DOI: 10.1016/j.bjoms.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vital staining with iodine solution in reducing local recurrence after resection of dysplastic or malignant oral mucosa

Abstract: Abstract.The purpose of this retrospective study was to assess the efficacy of vital staining with iodine solution in reducing local recurrence in the resection of dysplastic or cancerous oral mucosa.The conventional group (a historical control group) underwent surgical resection of dysplastic or cancerous mucosa solely by direct inspection/palpation. The vital staining group did with the aid of vital staining with iodine solution.Seven of 25 patients (28.0%) in the conventional group experienced recurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
6
0
5
Order By: Relevance
“…Chaudhari et al (2013) conducted a study on male inmates, and suggested that Lugol's iodine was highly effective as a screening tool for oral PMDs and oral cancer in inmate populations. Lugol's iodine staining during surgery can determine surgical resection margins, reduce local recurrence and improve survival in patients with epithelial dysphasia or malignant lesions (Umeda et al 2011;Kurita et al 2012). Maeda et al (2010) applied colorimetric analysis to analyze the color of unstained lesions in relation to the histopathologic findings, they made a color chart and proposed a possible histological diagnosis based on the measured colors of the unstained lesions.…”
Section: Lugol's Iodine Stainingmentioning
confidence: 99%
“…Chaudhari et al (2013) conducted a study on male inmates, and suggested that Lugol's iodine was highly effective as a screening tool for oral PMDs and oral cancer in inmate populations. Lugol's iodine staining during surgery can determine surgical resection margins, reduce local recurrence and improve survival in patients with epithelial dysphasia or malignant lesions (Umeda et al 2011;Kurita et al 2012). Maeda et al (2010) applied colorimetric analysis to analyze the color of unstained lesions in relation to the histopathologic findings, they made a color chart and proposed a possible histological diagnosis based on the measured colors of the unstained lesions.…”
Section: Lugol's Iodine Stainingmentioning
confidence: 99%
“…Available studies reported that the examination of the oral mucosa can be performed by staining with rose Bengal, already widely used to diagnose various ocular surface disorders [22,23], methylene blue, recently proposed for screening gastrointestinal or prostate tumours because it seems less toxic to the human [24,25] and Lugol's solution, used to detection esophageal, gastrointestinal and gynecological abnormalities [26][27][28]. However, the more common vital stain in oral medicine is the toluidine blue (TB), a vital acidophilic metachromatic stain of the thiazine group that has been effectively used in nuclear staining because of its binding to DNA nucleic acid.…”
Section: Vital Stainingmentioning
confidence: 99%
“…Por este motivo o uso de métodos de auxílio diagnóstico para facilitar a visualização das áreas alvo, tanto para biópsias quanto para remoção cirúrgica, pode ser indicado. A relevância das margens cirúrgicas nos casos de lesões que apresentam displasia e carcinoma in situ em relação ao prognóstico do paciente já é bem conhecida (Weijers et al, 2002;Kurita et al, 2012).…”
Section: Lista De Quadrosunclassified
“…A semiotécnica para o atendimento dos pacientes com lesões brancas na mucosa oral, alguns autores sugerem a realização rotineira de exame clínico minucioso juntamente com os métodos auxiliares: azul de toluidina a 1% (Martin et al, 1998;Guneri et al, 2011;Mehrotra;Gupta, 2011), citologia esfoliativa (Guneri et al, 2011), quimioluminescência (Epstein et al, 2008), fluorescência tecidual, VELscope®, (Mishra, 2012), solução de lugol (Kurita et al, 2012), microscopia confocal reflectante e a realização de biópsia de áreas suspeitas (Joseph, 2002).…”
Section: Lista De Quadrosunclassified
See 1 more Smart Citation